Pengaruh Brand Image, Brand Love dan Word of Mouth Terhadap Keputusan Pembelian Konsumen Produk Skincare Scarlett Whitening - Siti Masita; Kustoro Budiarta (CV. Ulil Albab Corp, 2024)
This study aims to determine the Influence of Brand Image, Brand Love and Word Of Mouth on Consumer Purchase Decisions of Scarlett Whitening Skincare Products. The population in this study is all consumers Scarlett Whitening whose sample size in this study is 120 peoples. The data analysis technique used Multiple Linear Analysis, the sampling technique using Purposive Sampling. The results show that (1) There is a positive and significant influence between Brand Image on Consumer Purchase Decisions of Scarlett Whitening Skincare products, (2) There is a positive and significant influence between Brand Love on Consumer Purchase Decisions of Scarlett Whitening Skincare products, (3) There is a positive and significant influence between Word Of Mouth on Consumer Purchase Decisions of Scarlett Whitening Skincare, (4) There is a positive and significant influence between Brand Image, Brand Love, and Word Of Mouth on Consumer Purchase Decisions of Scarlett Whitening Skincare products.